K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

NV
6 tháng 5 2019

\(y'=2019\left(x^2+x+1\right)^{2018}.\left(x^2+x+1\right)'=2019\left(x^2+x+1\right)^{2018}\left(2x+1\right)\)

\(y'=x'.sinx+x.\left(sinx\right)'=sinx+x.cosx\)

6 tháng 5 2016

banhhahaheheoebanhquabucminhbucquaeoeohagianroihehe

5 tháng 6 2016

y'= \(3x^2\)-2

NV
9 tháng 6 2020

a/ \(y'=2\left(2x^3-1\right).\left(2x^3-1\right)'=12x^2\left(2x^3-1\right)\)

b/ \(y'=2\left(1-x\right)\left(1-x\right)'=2\left(x-1\right)\)

c/ \(y'=\left(8x+1\right)\left(2x-3\right)+2\left(4x^2+x+1\right)\)